Improvement of mesoporosity of carbon cryogels by acid treatment of hydrogels - Kraiwattanawong, Kriangsak; Mukai, Shin R.; Tamon, Hajime; Lothongkum, Anchaleeporn W. (My University, 2008)
Wattle tannin-furfural (TFu) gels are synthesized by the sol-gel polycondensation of wattle tannin with furfural by using sodium hydroxide as a catalyst and cured at 363 K. After cured, the TFu hydrogels are treated in hydrochloric acid (HCl) solutions with various variables as follows: aging temperature, HCl concentration and pH. TFu cryogels aged are then freeze-dried and pyrolyzed under an inert atmosphere to obtain TFu carbon cryogels. The TFu and carbon cryogels were characterized by N2 adsorption and scanning electron microscope. The high HCl concentration yields the increase of mesopore volume almost twice especially at high temperature and the mesopore size distribution can be greatly developed sharper and narrower when the high concentration of HCl or/and the high temperature are used. Moreover, this method is the versatile approach for developing the mesopore structure of the low and high porous TFu hydrogels and has no serious problem of weight loss after treatment. © 2008 Elsevier Inc. All rights reserved.
Keywords: Acid treatment; Adsorption; Porosity; Porous carbon; Pyrolysis